Brother against Brother: Early Refutation of Wahhabism by the 18th-century Hanbali Scholars - Fata, Badrus Samsul; Ismail, Idznursham (UIN Sunan Kalijaga Yogyakarta, 2022)
Wahhabism has been a source of intergenerational controversies among sunnī madhabī scholars and even among respected Hanbali scholars themselves, initially from its rise in the 18th century until the date. Muḥammad b. ‘Abd al-Wahhāb’s fatwas have drawn sharp critiques and refutations by Hanbali scholars, particularly those regarding tawḥīd ulūhiyyat, which justifies declaring others as infidel-apostates (kāfir murtadd). Other contested fatwas include those on Muslim practices of seeking blessings (tabarruk), seeking intermediaries (tawassul), visiting graves (ziyārat), and seeking help (istighāthah). Muḥammad b. ‘Abd al-Wahhāb and his followers have theologically deemed these practices of major idolatry (as-shirk al-akbar) and have erred and biased in proclaiming his Wahhabism as the true successor to Ibnu Taymiyya, Ibn Qayyim al-Jawziyya and even manhaj of Ahmad b. Hanbal. In this regard, this article portrays the refutations and rebuttals by Hanbali scholars of Muḥammad b. ‘Abd al-Wahhāb and his early Wahhabism based on primary sources. The discussion describes theological examinations and counter-narrative campaigns against Wahhabism initiated by the 18th-century Hanbali scholars. The findings show that the majority of Hanbali scholars at the time refuse the teachings of Wahhabism and argue that the fatwas of Wahhabi scholars on the notion of ulūhiyyat, tabarruk, tawassul, ziyārat, and istigāthah are irrelevant and disconnected from the intellectualism of Hanbali scholars.